Karate-do gyaku-zuki tekniğinde itiş bacağı ile vuruş kolunun ilişkisinin incelenmesi - Bakacak, Ahmet (My University, 2021)
Amaç: Bu çalışmanın amacı Karate-do Kihon ve Kata uygulamaları için, Gyaku Zuki (GZ) tekniğinde bacak itişinin hareket örüntüsüyle ilişkilendirilerek ardışık eklem ivmeleri ve yumruk ivmesi açısından değerlendirilmesidir. Metot: Çalışmaya yaş ortalaması 25,5 (±8,98), kilo ortalaması 72.48 kg (± 16,99), boy ortalaması 172,85cm (±8,05) ve ortalama 13.10 yıl (±6,9) Karate geçmişi olan 5 kadın ve 15 erkek toplam 20 siyah kuşak sporcu gönüllü olarak katılmıştır. Ölçümler ısınmadan sonra gerçekleştirilmiştir. Her sporcu Gyaku Zuki tekniğini arkadaki dizin (1. varyasyon) ve ekstansiyon (2. varyasyon) olduğu iki farklı durumda maksimum eforla 5’er kez gerçekleştirmiştir. Katılımcılar kuvvet platformu üzerinde Gyaku Zuki uygularken, aynı esnada ivme ölçerle eklem ivmeleri ölçülmüştür. Bulgular: Sporcuların vuruş esnasında arkadaki itiş dizinin fleksiyon olduğu ve ekstansiyon olduğu durumlarda maksimum itiş kuvvetleri arasında anlamlı farklılık bulunmuştur (p<0,000). Varyasyonlar arasındaki maksimum yumruk ivmeleri kıyaslandığında anlamlı farklılık bulunmuştur (p<0,000). 2. varyasyon için maksimum yumruk ivmesinde ulaşılan ortalama değer (210,78 m/ s2) iken, 1. varyasyon için maksimum yumruk ivmesinde ulaşılan ortalama değer (240,86 m/ s2) olarak bulunmuştur. Sporcular, benzer biçimde sıralı eklem ivmelerinde düşükten yükseğe doğru aynı eklem sıralamasını izlemiştir. Sonuç: Kata ve Kihon uygulamaları için Gyaku Zuki tekniğinde bacak itişine dayandırılarak uygulanan tekniğin hareket örüntüsüne bağlı eklem ivmeleri ve yumruk ivmesi açısından daha başarılı teknikle sonuçlandığı düşünülmektedir.

Objective: The aim of this study is to investigate the leg thrust in terms of sequential joint accelerations and punch acceleration in Gyaku Zuki (GZ) Technique for Karate-do Kihon and Kata practice by associating it with the movement pattern. Method: A total of 20 black belt athletes (5 females and 15 males) were voluntarily recruited in this study. Mean age 25,5 (±8,98), mean weight 72.48 kg (± 16,99), mean height 172,85cm (±8,05), and mean experience 13.10 years (±6.9). The measurements were recorded after the warm-ups. Each athlete applied the Gyaku Zuki technique a total of five times with a maximum effort in two different positions in which the back knee flexed (1. variation) and extended (2. variation). As the participants applied Gyaku Zuki on a force platform, joint accelerations were measured with accelerometers. Results: A significant difference was found between the maximum thrust forces of the athletes when the rear thrust knee was flexed and extended during the punch (p<0.000). When the maximum punch accelerations were compared between the different variations, a significant difference was found (p<0.000). While the mean value at maximum punch acceleration for 2nd variation was (210.78m/ s2), the mean value reached at maximum punch acceleration for 1st variation was (240.86m/ s2). Athletes similarly followed the same joint sequence from low to high in sequential joint accelerations. Conclusion: It is thought that the technique applied based on the leg thrust in the Gyaku Zuki technique for Kata and Kihon applications results in a more succesful technique in terms of joint accelerations and punch acceleration depending on the movement pattern.
Investigation of the relationship of thrust leg and strike arm in karate-do gyaku-zuki technique
Keywords: Acceleration; Combat sports; Force; Gyaku zuki; İvme; Karate; Kuvvet Karate; Mücadele sporları